2023
DOI: 10.1186/s13293-023-00498-8
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A in AgRP neurons is required for sex-dependent regulation of feeding and thirst

Abstract: Background Fatty acid metabolism in the hypothalamus has an important role in food intake, but its specific role in AgRP neurons is poorly understood. Here, we examined whether carnitinea palmitoyltransferase 1A (CPT1A), a key enzyme in mitochondrial fatty acid oxidation, affects energy balance. Methods To obtain Cpt1aKO mice and their control littermates, Cpt1a(flox/flox) mice were crossed with tamoxifen-inducible AgRPCreERT2 mice. Food intake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…We previously observed that Cpt1a KO mice had reduced projections from AgRP neurons to the paraventricular nucleus (PVN) of the hypothalamus, enhancing the HPA axis and sympathetic tone. We also observed a decrease in blood levels of testosterone (Zagmutt et al, 2023).…”
Section: Cpt1a Ko Mice Exhibit Protection Against Aging Declinesupporting
confidence: 60%
See 1 more Smart Citation
“…We previously observed that Cpt1a KO mice had reduced projections from AgRP neurons to the paraventricular nucleus (PVN) of the hypothalamus, enhancing the HPA axis and sympathetic tone. We also observed a decrease in blood levels of testosterone (Zagmutt et al, 2023).…”
Section: Cpt1a Ko Mice Exhibit Protection Against Aging Declinesupporting
confidence: 60%
“…In addition, the ability of aged mice lacking Cpt1a to develop the same level of exercise capacity as adult mice is remarkable because these animals do not show any features characteristic of decline due to aging (Graber et al, 2021). This may be a consequence of the reduced food intake observed in Cpt1a KO mice (Zagmutt et al, 2023), similar to that observed in mice under dietary restriction (Fahlström et al, 2012;Peters et al, 2022). Furthermore, in the last decade, AgRP neurons have been associated with neuronal circuits of nonfeeding behavior, including those related to reward, anxiety, and compulsive behavior (Dietrich et al, 2015;Miletta et al, 2020).…”
Section: Agrp Neurons Require Cpt1a To Modulate Exercise Performance ...mentioning
confidence: 99%
“…To our knowledge, this is the first report of AgRP neuron stimulation causing sexually dimorphic feeding behavior, although an interesting recent study demonstrated sex differences in how stress changes preference for AgRP neuron stimulation: a subset female, but not male, mice prefer rather than avoid AgRP neuron stimulation after stress [31]. Further, there are known sex differences regarding the function of metabolic signaling pathways in AgRP neurons [32; 33] and Agrp protein expression [3436]. Because AgRP neuron stimulation increases food intake equally in males and females (Figure 2G), it will be interesting to investigate the mechanisms that underlie the observed sex differences specifically related to FNL.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotaxic surgery to target VMH was carried out with the following coordinates: 1.5 mm posterior from Bregma, ± 0.5 mm lateral to midline and 5.8 mm deep. Purified AAVs expressing mCherry under Cre activity (AAV-CRE-mCherry) (Zagmutt et al, 2023) were injected bilaterally over 10 minutes through a 33-gauge injector connected to a 5 µL Hamilton® Syringe (65460-02, Hamilton Company, Reno, USA) and an infusion pump. 0,4 nL with a viral titer of 1,23x10 12 pfu/mL were infused in each injection site.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify the adipocyte area, three representative images from each adipose tissue section were taken with a 20x objective using a high-sensitivity camera (Leica MC 190 HD Camera) and microscope. Images were analyzed with the Adiposoft software as described in Zagmutt et al, 2023. Images were analyzed and adipocytes were highlighted if they met the following criteria:…”
Section: Adipose Tissue Histopathology and Adipocyte Area Measurementmentioning
confidence: 99%